2021
DOI: 10.3390/agronomy11050924
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Crop Residues for Bioconversion

Abstract: Decreasing the dependence on fossil resources as raw materials for the production of fuels, platform chemicals, and commodities is an imperative requirement of today’s industry and society in order to alleviate the threats related to climate change [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Many pretreatment approaches have been developed as a result of intense research in the area, and some of the most effective methods have been validated at demonstration scale ( Galbe and Wallberg, 2019 ). Research on different raw materials has shown that the effectiveness of pretreatment is feedstock-dependent, and that the effects of a given method can diverge for different types of lignocellulosic biomass ( Martín, 2021 ). Low capital expenditures (capex) and operational expenditures (opex) are key criteria for industrially viable pretreatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Many pretreatment approaches have been developed as a result of intense research in the area, and some of the most effective methods have been validated at demonstration scale ( Galbe and Wallberg, 2019 ). Research on different raw materials has shown that the effectiveness of pretreatment is feedstock-dependent, and that the effects of a given method can diverge for different types of lignocellulosic biomass ( Martín, 2021 ). Low capital expenditures (capex) and operational expenditures (opex) are key criteria for industrially viable pretreatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Lignocellulosic biomass represents a practically infinite feedstock source for satisfying the demands of the industry, and could thus contribute to achieving a carbon-neutral future and alleviating the current threats related to climate change. In previous collections, we compiled relevant contributions on the chemistry and technology of lignocellulosic biomass [2] and on the bioconversion of crop residues to biofuels and other bio-based products [3]. With this Special Issue, we present a new collection of articles dealing with cutting-edge topics in the field of lignocellulosic biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, disposal by burning is one of the chief methods for coping with the accumulation of plant residues. However, this widespread practice is against sustainability principles, contributes substantially to air pollution [ 8 ], and results in a considerable waste of biomass resources that are highly valuable for generating materials, fuels, and chemicals of high economic and social value [ 9 ].…”
Section: Introductionmentioning
confidence: 99%